American literature - Bertens, Hans (Routledge, 2014)
Includes bibliographical references and index; Beginnings to 1810 -- 1810-1861 -- 1865-1918 -- World War I to the Cold War: 1914-1948 -- After the war -- The end and return of history: 1980- 2010